Implementasi Pendidikan Sufisme dalam Pendidikan Islam - Munirah Munirah (LPPM IAIN Sultan Amai Gorontalo, 2019)
This article aims to reveal the implementation of Sufism education in Islamic education. The method used is qualitative literature study. The results of the study show that tasauf has great potential because it can offer liberation of spiritual crises, invites people to know themselves, to get to know their God better to obtain his guidance. This is a guideline in human life that is very effective, so it is not tossed around by the storms of life. With the tasauf approach in this era, more emphasis on the social moral reconstruction of the community so that the emphasis is more intense on strengthening faith in accordance with the principles of Islamic creed, and the evaluation of worldly life is as important as ukhrawi life in efforts to anticipate the era of globalization.